Factors predicting mobile learning utilization among undergraduates in a public university, Oman - Altabib, Shaima' Mohammad Abdallah (2017)
Recently, the use of mobile learning has become widespread. Mobile learning refers to the use of mobile or handheld devices such as mobile phones, laptops, smart phones, and tablets in order to support learning at any place and at any time in teaching and learning. Despite the advantages of using mobile learning for learning purposes in enhancing the quality of learning, it is not fully used in higher education in Oman. The review of previous studies shows that despite much research on mobile learning, only a few of the studies have investigated students’ utilization level. Hence, the purpose of this study was to identify whether the predictive factors significantly influenced the utilization of mobile learning. Moreover, in determining the level of the utilization of mobile learning, the study also sought to investigate the role of behavioral intention as a mediator as well as gender and field of study as moderators, and finally, to develop a model for the utilization of mobile learning. This study not only tested the Unified Theory of Acceptance and Use of Technology (UTAUT) itself, but also combined some factors from Mobile Learning Acceptance Model (MLAM) and Liew’s et al. Model which are both specific models for mobile learning.